The Role of Sustainable Design in Interior Spaces for Kindergartens - Halla Hameed Salih; Raja Saadi Lafta (الاكاديمي)
Governments and international institutions have encouraged their citizens to embrace the principle of sustainability in designing architecture and interior spaces. Interior design, incorporating new and contrasting concepts, is a crucial issue for designers and developers, especially with emerging challenges in the vast practical and technical advancements influencing design content and spatial arrangements. This research addresses the extent to which interior designers comprehend the concept of contrast and its sustainable role in designing interior spaces for kindergartens, achieving functionality for sustainability. The significance of providing a healthy environment for children in kindergartens, a key concern for interior designers in line with sustainable contrast, is emphasized. The theoretical framework in the second chapter covers the concepts of contrast and its application in interior design, along with sustainability and its role in designing interior spaces. The third chapter outlines the research methodology, relying on a descriptive approach to analyze the research model. The fourth chapter presents the research results, highlighting that natural and artificial lighting systems used in educational and service spaces in kindergarten environments achieve functional and aesthetic aspects. The conclusions emphasize that designing for a sustainable environment is a global design trend focusing on the vital relationship between humans and the interior environment through sustainable contrast